Philosophers of Belarusian State University and philosophers of Russia: forms of cooperation (to the 100th anniversary of the Belarusian State University) - Dudchik, Andrey Yu.; Liahchylin, Anatoly A.; Saiganova, Veronika S. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article provides an overview of the interaction between philosophers of Belarusian State University and philosophers of Russian organisations during the 100th anniversary of the university’s existence in various periods of Soviet times and at the present stage. The experience of Belarusian State University is as an interesting example of a new university, created in Soviet times already and being the leading university of the BSSR. Starting from the first years of formation and further (within the framework of general periodisation), the formation of professional philosophers of Belarusian State University can be traced in the context of their relationship with Russian researchers. The main attention is paid to specific personalities of the philosophical community of Belarusian State University – doctors of philosophy mainly, who have actively interacted with leading Russian philosophers throughout the century. The variety of forms and types of interaction between the philosophers of the two countries (education and scientific supervision, discussions and defense of PhD dissertations, joint research and publications, etc.) is demonstrated, the specificity of the mobility of philosophers in Soviet times is revealed with examples from history. It is shown that the interaction between the philosophers of the two countries covered most areas of modern philosophical knowledge, including both philosophy and methodology of scientific knowledge, traditionally popular among Belarusian researchers, and research in the field of the history of philosophy, logic, later – social philosophy, sociology and philosophy of culture. In addition to innovative philosophical research, cooperation in the development of fundamental philosophical education and the development of general education courses in philosophy is also important. The institutional aspects of interaction between the philosophers of the two countries deserves special attention, which manifests itself in joint research, scientific and educational publications, and joint events.
Keywords: Belarus; BSSR; Belarusian State University; Belarusian philosophy; Soviet philosophy; Russian philosophy